RAID1-memory high reliability with time redundancy - Городній, О. В.; Галузинський, Г. П. (Problems of Informatization and Control, 2015)
RAID1-storage system with redundant memory cells drive and temporal redundancy is considered. The degree of increase of reliability of information storage in such storage devices is defined